1981
DOI: 10.1111/j.1532-5415.1981.tb02391.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin Concentrations in Venous versus Capillary Blood of Geriatric Patients

Abstract: In 15 elderly patients who had seizure disorders, venous blood (standard venipuncture) was compared with capillary blood (finger lancet puncture) as the source of the specimen for determination of serum phenytoin concentration. The values obtained by the two procedures were similar (r = 0.99). The mean serum phenytoin levels in the venous samples was 17.3 micrograms/ml, and in the capillary samples 17.0 micrograms/ml; the paired t test showed no statistical difference. Either method provides an adequate blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Historically, the finger lancet punctures became a feasible option for clinical care with the development of microvolume assay methods that permitted the use of small blood volumes. 21 Aminoglycoside concentrations determined from finger lancet punctures were thought to be similar to concentrations determined from venipunctures, except that finger lancet punctures minimized blood loss in patients compared with venipunctures. 22,23 However, methods used to assess this similarity were insufficient to establish agreement and did not address the drawbacks of finger lancet punctures.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the finger lancet punctures became a feasible option for clinical care with the development of microvolume assay methods that permitted the use of small blood volumes. 21 Aminoglycoside concentrations determined from finger lancet punctures were thought to be similar to concentrations determined from venipunctures, except that finger lancet punctures minimized blood loss in patients compared with venipunctures. 22,23 However, methods used to assess this similarity were insufficient to establish agreement and did not address the drawbacks of finger lancet punctures.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of microvolume analytical techniques makes it possible to assay small volume capillary samples, collected by a finger lancet puncture. Capillary sampling has been used interchangeably with venous sampling for the determination of theophylline (Frazer et al, 1983), phenytoin (Umstead & McKernon, 1981), and various biochemical and haematological parameters (Blumenfield et al, 1977;Stuart et al, 1974). However, significant venous-arterial concentration differences have been identified with a number of other drugs (Chiou & Lam, 1982) (Schentag et al, 1978), studies in rabbits have demonstrated that tobramycin distributes slowly into interstitial fluid with peak concentrations attained 34 h after peak concentrations in serum (Gerding et al, 1976;Carbon et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The commonly used EMIT assay can be performed in a few minutes and requires a sample volume of 50 ,ul or less (Dale et al, 1984). With the advent of micro-volume assay methods, capillary blood sampling using a finger lancet puncture technique furnishing a whole blood sample volume of 100-800 ,ul (Umstead & McKernon, 1981) (Umstead & McKernon, 1981;Frazer et al, 1983;Blumenfield et al, 1977). The advantages of using capillary samples are particularly evident in the geriatric and paediatric patient.…”
Section: Introductionmentioning
confidence: 99%
“…Коэффициент позволяет использовать уже сертифицированные на венозной крови методики ТЛМ в приложении их к методам ТЛМ, использующим капиллярную кровь, путём простого умножения полученных показателей на этот коэффициент. Для некоторых лекарственных препаратов этот коэффициент был получен эмпирическим путем и, как правило, близок к 1 (от 0,84 до 1,13 [57,[62][63][64][65][66][67][68][69][70]). Следует также отметить, что для лекарственных веществ, для которых эмпирически коэффициент пересчета не установлен, можно применять формулу пересчёта, известную как поправку на гематокрит [61,[71][72][73][74][75][76][77].…”
Section: использование капиллярной крови для пм-тлмunclassified